2016
DOI: 10.1007/s12288-016-0648-0
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between CXCR4 Gene Expression and Prognosis of Immune Thrombocytopenia in Children?

Abstract: Immune thrombocytopenia (ITP) is a common autoimmune disorder characterized by decreased platelet count (thrombocytopenia) and bleeding symptoms due to production of autoantibodies against platelets. Chemokines are molecules inducing chemotaxis and play an important role in megakaryopoiesis, including CXCR4 chemokine receptor. CXCR4 is expressed on cells of megakaryocytic series, especially platelets, and triggers several mechanisms in these cells. The purpose of this study was to evaluate the pattern of CXCR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Immune thrombocytopenic purpura is an autoimmune disorder that is associated with the peripheral destruction of platelets by autoantibodies against platelet GPs . The pathophysiology of ITP is heterogeneous and genetic background (such as the percentage of polymorphisms in immune system‐related genes), as well as aberrant expressions of some chemokine receptors and micro‐RNAs alongside antiplatelet antibodies, may play a crucial role in predisposition to ITP and even response to treatment . Moreover, impairment of the number and function of different immune cells can play an important role in the initiation and prolongation of ITP .…”
Section: Discussionmentioning
confidence: 99%
“…Immune thrombocytopenic purpura is an autoimmune disorder that is associated with the peripheral destruction of platelets by autoantibodies against platelet GPs . The pathophysiology of ITP is heterogeneous and genetic background (such as the percentage of polymorphisms in immune system‐related genes), as well as aberrant expressions of some chemokine receptors and micro‐RNAs alongside antiplatelet antibodies, may play a crucial role in predisposition to ITP and even response to treatment . Moreover, impairment of the number and function of different immune cells can play an important role in the initiation and prolongation of ITP .…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the chemokine receptors VLA‐4 (CD49d), CX3CR1 (CD181), and CXCR4 (CD184) are also increased on CTL of ITP patients . These receptors bind their ligands and cause CTLs shift from PB to BM, which leads to the recruitment of CTLs for platelet destruction and inhibition of megakaryocyte maturation in BM of patients, resulting in reduced platelet counts (Table ) . In ITP patients, it has been reported that increased IL‐27 levels, which causes decreased granzyme B production in CTL, reduces the platelet destruction and enhances the response to treatment of these patients .…”
Section: Abnormal Expression Of T‐cell CD Markers In Itpmentioning
confidence: 99%
“…[4][5][6] Therefore, it is important to predict the prognosis early so that treatment modification can be prepared. [7][8][9][10] Recently a meta-analysis 11 including several studies suggested that the levels of absolute lymphocyte count (ALC) were associated with the development of chronic ITP. However, it is well known that in childhood, the ALC levels vary with age.…”
mentioning
confidence: 99%
“…Prolonged disease course and long-term use of steroid inevitably affect children’s growth and bring great psychological burden to their families 4–6. Therefore, it is important to predict the prognosis early so that treatment modification can be prepared 7–10. Recently a meta-analysis 11 including several studies suggested that the levels of absolute lymphocyte count (ALC) were associated with the development of chronic ITP.…”
mentioning
confidence: 99%